The role of custom farming in agribusiness expansion in Argentina. Issue 3 (16th April 2022) - Sosa Varrotti, Andrea P.
ABSTRACT: This article aims to examine the role of custom farming in the expansion of the agribusiness model in Argentina, and more specifically, of machinery contractors incorporated into productive 'networks' led by large-scale sowing pools and companies. It treats dispossession as being in a dialectic relationship to productivity, thus posing the question of labour as a core discussion in this process. Its purpose is to provide an insight into agribusiness that, while remaining critical, can be constructive for discussing the development implications of this model in the public arena.